KERAGAAN USAHATANI PADI GOGO PADA PROGRAM PENGELOLAAN HUTAN BERSAMA MASYARAKAT DI KESATUAN PENGELOLAAN HUTAN INDRAMAYU - Linda Wulandari; Kuswarini Kusno (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
PHBM is a system of forest resource management conducted jointly with PerumPerhutani and people from villages forest. One of the village that implement the program is Jatimunggul village. In the implementation, the program facing some trouble because the rural community was not agree with management takeover by Perhutani. As the result the farmers is protesting about forest land which considered belongs to them. The purpose of this study was to determine the performance of upland rice that held by farmers from Perhutani Forrest area at Jatimunggul Village. Qualitative research design is supported by quantitative data with case study research techniques. The results show that the cultivation of upland rice in PHBM Program still using traditional tools. There are some processes upland rice farming that involving another party such as: procurement of capital which is 20% come from self-capital and 80% from capital loan the middleman, site planning process and commodity that involving Perhutani, and marketing of the upland rice products that involving the middleman. The average income of the upland rice farmer per hectare each years is Rp. 23.800.333, meanwhile the income is Rp. 9.402.985 with average of production is 3.543 kg/ha. The average of total cost that the farmer spend is Rp. 15.112.352 consisting of variable cost value of Rp. 14.480.450 and fixed cost Rp. 631.902. when compared with the secondary revenue data of upland rice at Sukasari Villages at 2014 then the revenue from upland rice at Jatimunggul Village is higher Rp. 10.710.333 or differ by 45% compared with revenue from Sukasari Villages. PHBM Program not only give economics benefit, but also benefit at socials such as for employment, but the benefit for the environment not fully completed yet.